Pengaruh Kesadaran Merek dan Kepercayaan Merek Terhadap Loyalitas Pelanggan WINSTON Indonesia - Agus Kusuma Jaya (Jurnal Strategi Pemasaran, 2014)
Surabaya is the second largest city in Indonesia with the rapid growth in property, especially land for housing. This can also be seen from the rise of the new office of the growing property brokerage, to serve its customers in meeting the needs of his or her property. Grab the loyalty of consumers and defend it are the things that are important to property brokerage in Surabaya. Therefore this study is intended to determine the extent of the influence of Brand awareness and Brand trust of customer loyalty WINSTON Indonesia. In addition, this research also aims to determine whether the variables which most influence on customer loyalty.The research was carried out quantitatively, using techniques of causal analysis with the method of Structural Equation Model – Partial Least Square SEM-PLS with as many as 100 respondents. Engineering data retrieval is performed also with non-probability sampling, purposive sampling technique. The survey results revealed that Brand awareness and Brand trust influencing Loyalty customer of WINSTON Indonesia. The dominant influence is Brand trust to Loyalty customer.